STRATEGI PEMASARAN TOUR PACKAGES DI BIRO PERJALANAN WISATA BARAMA INTERCITY TOUR & TRAVEL YOGYAKARTA - , ANISA NANINDRA MAHASTRAJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Barama Intercity Tour & Travel is a travel agency that provides a variety of tour packages both domestic and foreign. The packages are offered attractive and the price is affordable. Currently, the marketing strategies used by Barama Intercity Tour & Travel is market analysis and marketing mix for business services. This final task titled is \"Strategi Pemasaran Paket Wisata di Barama Intercity Tour & Travel Yogyakarta\". The final task is descriptive-qualitative aims to determine the marketing strategies in marketing and promoting tour packages in Barama Intercity Tour & Travel, to make better marketing and to attract potential customers to purchase travel packages Barama Intercity Tour & Travel. Based on the research results, the strategic steps taken by the management Barama Intercity Tour & Travel in marketing travel packages that should maximize the marketing mix strategies that already exist, create innovative tour packages and different from the others, promote tour packages in various media, both print and electronic. And the most important is recruiting marketing staff so that all existing marketing strategy to be effective and maximum. In addition, Barama Intercity Tour & Travel can broaden the market segmentation that will be targeted marketing. Thus, managers Barama Intercity Tour & Travel in the marketing and promotion of travel packages need to make a new breakthrough for creating innovative tour packages like never before. It aims to increase the potential consumers who buy products travel packages Barama Intercity Tour & Travel and to face the competition among tour operators in Yogyakarta and surrounding areas.